METTL13 is essential for the survival of acute myeloid leukemia cells by regulating MYC - Kui Zhao; Hanyue Zhang; Shuoting Wang; Yuhang Zhou; Zhishuai Zhang; Baoqiang Kang; Huaisong Lin; Yanqi Zhang; Jiaming Gu; Carla Pantoja; Lingling Liu; Yi He; et al. (Cell Death Discovery)
Abstract Recently, some methyltransferase-like (METTL) proteins have been found to play crucial roles in the development of acute myeloid leukemia (AML) through mediating RNA modifications, such as METTL3/14/16 mediated N6-methyladenosine (m6A) and METTL1 mediated N7-methylguanosine (m7G). However, the roles of other METTL proteins in AML progression remain unknown. Here, we examined the expression levels of all METTL members in AML samples and showed that METTL13 was increased in AML and positively correlated with poor prognosis. Moreover, METTL13 deficiency impaired AML cell proliferation capability in vitro, improved the survival of AML cell line xenograft immune-deficient mice, and reduced tumor infiltration in vivo. Mechanistically, MYC was downregulated after METTL13 knockdown and forced expression of MYC rescued the cell proliferation defect in METTL13-deficient AML cells. Our findings uncover the critical role of METTL13 in the survival of AML cells and identify MYC as a potential downstream target of METTL13. This work highlights METTL13 as a promising candidate target for AML therapy.